2009
DOI: 10.1029/2008jd011532
|View full text |Cite
|
Sign up to set email alerts
|

Ice nuclei emissions from biomass burning

Abstract: Biomass burning is a significant source of carbonaceous aerosol in many regions of the world. When present, biomass burning particles may affect the microphysical properties of clouds through their ability to function as cloud condensation nuclei or ice nuclei. We report on measurements of the ice nucleation ability of biomass burning particles performed on laboratory‐generated aerosols at the second Fire Lab at Missoula Experiment. During the experiment we generated smoke through controlled burns of 21 biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
234
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(253 citation statements)
references
References 68 publications
16
234
3
Order By: Relevance
“…IN/N >0.1 ratios were also less than 0.01 % with IN/N >0.5 ratios of ∼0.03-0.07 % and ∼0.2-2 % for CFDC measurements at −32 • C and −34 • C, respectively. Previous laboratory measurements of immersion/condensation freezing of sagebrush combustion aerosols at −30 • C showed a IN/CN ratio below 0.0025 % for five out of seven samples, with a ratio of 0.25 % for two out of seven samples (Petters et al, 2009b), consistent with the ratios measured herein. Considering plume 0.1-1.0 µm unreacted mineral dust number fractions, measured by the A-ATOFMS, of <0.4 % and activation of ∼6-20 % of mineral dust as ice nuclei (Field et al, 2006;Prenni et al, 2009), an IN/N >0.1 fraction of <0.08 % would be predicted, suggesting that mineral dust cannot be ruled out as the source of IN.…”
Section: Ice Nucleisupporting
confidence: 78%
See 3 more Smart Citations
“…IN/N >0.1 ratios were also less than 0.01 % with IN/N >0.5 ratios of ∼0.03-0.07 % and ∼0.2-2 % for CFDC measurements at −32 • C and −34 • C, respectively. Previous laboratory measurements of immersion/condensation freezing of sagebrush combustion aerosols at −30 • C showed a IN/CN ratio below 0.0025 % for five out of seven samples, with a ratio of 0.25 % for two out of seven samples (Petters et al, 2009b), consistent with the ratios measured herein. Considering plume 0.1-1.0 µm unreacted mineral dust number fractions, measured by the A-ATOFMS, of <0.4 % and activation of ∼6-20 % of mineral dust as ice nuclei (Field et al, 2006;Prenni et al, 2009), an IN/N >0.1 fraction of <0.08 % would be predicted, suggesting that mineral dust cannot be ruled out as the source of IN.…”
Section: Ice Nucleisupporting
confidence: 78%
“…During all plume sampling, the maximum observed IN/CN ratio (0.008 %) was <0.01 %, estimated by Petters et al (2009b) as likely to strongly perturb IN concentrations on a regional scale. IN/N >0.1 ratios were also less than 0.01 % with IN/N >0.5 ratios of ∼0.03-0.07 % and ∼0.2-2 % for CFDC measurements at −32 • C and −34 • C, respectively.…”
Section: Ice Nucleimentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of aerosols in this region originate from biomass burning in the Amazon region (14). The IN potential of these aerosols has been observed in many field experiments (15,(16)(17)(18)(19) example, reported that the reduction in the size of cloud droplets and the delay in the onset of precipitation within smoky warm clouds in the Amazon region allow more aerosols and moisture to reach higher altitudes by means of updrafts. This may also be enhanced by the high terrain of the Andes where the very small SCF values appear.…”
Section: Observed Supercooled Clouds and The Relations With Tempera-mentioning
confidence: 99%